Grasses and Grassland Aspects - Missiakô Kindomihou, Valentin (IntechOpen, 2020)
Renewed attention is being given to global agricultural productivity such as food security, food prices, financial viability of farm businesses under rising costs, declining availability and affordability of critical inputs including suitable land, etc.Thus, farming systems need to combine space maintenance and food herds in rural areas. Facing these new challenges, interest in grasses and grasslands as important forage systems has increased over the past 30 years, due to their economic, environmental, and ecological properties. A better use of economic and ecological potentials requires an understanding of their functions, and the development of tools for feeding herds, managing space, maintaining biodiversity, and limiting pollution.This book intends to provide the reader with the latest aspects on grasses and grassland for the well-being of farming systems.